Edge contact dependent spin transport for n-type doping zigzag-graphene with asymmetric edge hydrogenation - Deng, Xiaoqing (Nature Publishing Group, 2014)
Spin transport features of the n-type doping zigzag graphene nanoribbons (ZGNRs) with an edge contact are investigated by first principle methods, where ZGNRs are C–H(2) bonded at one edge while C–H bonded at the other to form an asymmetric edge hydrogenation. The results show that a perfect spin filtering effect (100%) in such ZGNR nanojunctions can be achieved in a very large bias region for the unchanged spin states regardless of bias polarities, and the nanojunction with a contact of two C–H(2) bonded edges has larger spin polarized current than that with a contact of two C–H bonded edges. The transmission pathways and the projected density of states (PDOS) demonstrate that the edge of C-H(2) bonds play a crucial role for the spin magnetism and spin-dependent transport properties. Moreover, the negative differential resistance (NDR) effect is also observed in the spin-polarized current.